Latin loan-words in English place-names: a study of their linguistic, archaeological and chronological contexts, with special reference to Latin vīcus and Old English wīc - Stanley, Nigel Edward (2024)
In the English place-name Wickham, derived from Old English wīc‒hām, the first element is OE wīc, loaned from Latin vīcus. This thesis explores in depth the hypothesis proposed by various place-name scholars, especially by Margaret Gelling from 1967‒97, that Wickham might refer to a Roman settlement site, and that in place-names such as Wickford, the specific wīc might sometimes refer to Roman settlement. Owing to a great increase in the number of Roman sites excavated since the 1970s, and the availability of information from sources such as the Portable Antiquities Scheme and Roman Rural Settlement project, this thesis is able to use modern archaeological knowledge unavailable to Gelling and twentieth-century place-name scholars, to explore the potential relationship between place-names and Roman archaeology.